Child Pornography Is Showing Participation a Person Under the Age of 18 in Sexual Intercourse - Siniša Franjić (Studies in Law and Justice, 2023)
Child pornography means any video or image showing a person under the age of 18 engaging in sexual intercourse, showing the genital or anal area of a person under the age of 18 for sexual reasons, or any document supporting sexual intercourse with minors. Child pornography is among the most widespread forms of crime on the Internet. Child pornography is spread by pedophiles to create a personal collection, exchange material with other pedophiles, or create new material and child prostitution. Child pornography is illegal in most world jurisdictions. Convictions for possession of child pornography also usually include prison sentences, but these sentences often translate into suspended sentences for perpetrators.